La necrópolis tardorromana de “El Tesoro” (Marchamalo, Guadalajara) - Abascal Palazón, Juan Manuel (Antigüedad y Cristianismo, 1991)
The localization of "El Tesoro" (Marchámalo, Guadalajara) is known, and mencioned in the arqueological bibliography, since its discovery in the last years of the nineteenth century. A late Roman necropolis, belonging to the group known as the "necropolis del Duero", has been brought to light, proving not only the continued use of the funeral space as such but also offers new information on the distribution of this type and its materials.